1987
DOI: 10.1099/0022-1317-68-3-871
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Replication of Hepatitis B Virus and the Localization of Virus Nucleocapsid Antigen (HBcAg) in Hepatocytes

Abstract: SUMMARYAccording to the localization of hepatitis B virus (HBV) core antigen (HBcAg), detected by the avidin biotin complex method, infected hepatocytes were classified into three types, i.e. those having nuclear (type I), nuclear and cytoplasmic (type II) or only cytoplasmic (type III) antigen. HBcAg-positive hepatocytes of all specimens (three) from non-specific reactive hepatitis and of most (five of seven) from chronic persistent hepatitis (CPH) patients were only type I; the other two CPH samples and all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Consistently, by use of polyclonal antibodies, it was observed that HBcAg localized mainly in the nuclei in patients with minor hepatitis activities and the nuclear HBcAg decreased significantly with concomitant increase of cytoplasmic HBcAg expression in patients with active hepatonecroinflammation [7]. Similar observations have been made by several other groups [8][9][10][11][12][13]. Intriguingly, these studies also showed that the presence of nuclear HBcAg was associated with high serum levels of HBV-DNA in spite of low hepatitis activities [2,[8][9][10]13].…”
Section: Introductionsupporting
confidence: 71%
“…Consistently, by use of polyclonal antibodies, it was observed that HBcAg localized mainly in the nuclei in patients with minor hepatitis activities and the nuclear HBcAg decreased significantly with concomitant increase of cytoplasmic HBcAg expression in patients with active hepatonecroinflammation [7]. Similar observations have been made by several other groups [8][9][10][11][12][13]. Intriguingly, these studies also showed that the presence of nuclear HBcAg was associated with high serum levels of HBV-DNA in spite of low hepatitis activities [2,[8][9][10]13].…”
Section: Introductionsupporting
confidence: 71%
“…In HepaRG cells, which can be infected with HBV, core has been detected in the cytoplasm and occasionally in the nucleus (Gripon et al, 2002). The localization of core in humans is also variable: Akiba et al (1987) and Sharma et al (2002) observed more frequent nuclear localization while others observed a mainly cytoplasmic core and/or capsid localization (Liu et al, 2009;Michalak & Nowosławski, 1982;Park et al, 1999;Petit & Pillot, 1985). In terms of disease and viral load, the majority of studies associate cytoplasmic capsids with high hepatocellular injury (Chu et al, 1995Kim et al, 2006;Naoumov et al, 1990) and a low level viraemia (Liu et al, 2009) while nuclear dominance is associated with high viral load and minor hepatitis activity .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, increased expression of viral antigen on hepatocytes due to high HBV replication leads to marked hepatitis (Chu et al 1985; Hsu et al 1987). On the other hand, we examined previously the form of HBV in hepatocytes by electron microscopy and reported that viral particles, including Dane particle and core particle, were observed in HBV carriers without hepatitis, but not in those with active liver disease (Akiba et al 1987). These facts suggest that the replication state of HBV may differ according to the disease activity.…”
mentioning
confidence: 99%